A cross-sectional study exploring levels of physical activity and motivators and barriers towards physical activity in haemodialysis patients to inform intervention development. Issue 12 (5th June 2021) - Sutherland, Sheera; Penfold, Rose; Doherty, Aiden; Milne, Zara; Dawes, Helen; Pugh, Christopher; Boulton, Mary; Newton, Julia L.
Abstract: Purpose: To describe physical activity (PA) levels and motivators and barriers to PA amongst haemodialysis (HD) patients and to identify an appropriate approach to increasing their PA. Methods: A cross-sectional mixed methods study conducted in a tertiary and satellite HD unit. One hundred and one participants aged 18 years and over, receiving regular HD for at least four months, were recruited. Patients with recent hospital admission or acute cardiac event were excluded. Participants completed health status (EQ-5D-3L™) and activity (Human Activity Profile (HAP)) questionnaires. A subgroup was invited to wear accelerometers and wearable cameras to measure PA levels and capture PA episodes, to inform subsequent semi-structured interviews on motivators and barriers. Semi-structured interviews were analysed using the framework method informed by constructs of the Health Belief Model. Results: 98/101 completed the study (66 males, 32 females). For 68/98 participants, adjusted activity scores from the HAP indicated "impaired" levels of PA; for 67/98 participants, the EQ-5D-3L indicated problems with mobility. Semi-structured interviews identified general (fear of falls, pain) and disease specific barriers (fatigue) to PA. Motivators included tailored exercise programmes and educational support from health care professionals. Conclusions: Participants indicated a need for co-development with healthcare professionals of differentiated, targeted exercise interventions. Implications for rehabilitation: Healthcare professionals should encourage and motivate haemodialysis patients to participate in physical activity (PA). As part of this approach, there is a need to increase patient knowledge of safe beneficial exercise activities and help individuals identify and overcome barriers. To allow for individualised approaches, clinical interventions should focus on other community activities that patients can do outside the dialysis clinic setting and utilise existing networks such as the British Renal Society Rehabilitation Network. The dialysis clinic provides professionals the opportunity to monitor and motivate patients. Relevant education is needed for staff about the benefits of PA and how to engage patients and their carers in safe and effective approaches.